Response of nitrogen content for some varieties of kenaf fiber (Hibiscus cannabinus L.) by applying different levels of potassium, boron and zinc - Salih, Rabar Fatah; Abdan, Khalina; Wayayok, Aimrun; Abdul Rahim, Anuar; Hashim, Norhashila (Elsevier, 2014)
The aim of this study was to determine the impact of the potassium, boron and zinc on the nitrogen of fiber. Two kenaf varieties namely; FHH 925 and 4383, were planted. Fertilizers (0, 100 and 150), (0, 1.0 and 1.5) and (0 and 5.0) kg/ha, for potassium, boron and zinc were added respectively. The best result was achieved for variety FHH 925 when potassium was added at level of 150 kg/ha, but regarding 4383 was when potassium, boron and zinc were applied at 150, 1.0 and 5 kg/ha, respectively. Based on the results potassium was really suitable for the kenaf.